2017
DOI: 10.1139/cjc-2016-0505
|View full text |Cite
|
Sign up to set email alerts
|

Probing the structural features that influence the mesomorphic properties of substituted dibenz[a,c]anthracenes

Abstract: We report the synthesis and mesophase characterization of a series of novel hexaalkoxydibenzanthracenes in order to probe the effect of side-chain length variation and substituents on the mesophase temperature range.A series of hexaalkoxydibenz [a,c]anthracenes (2a-i) with varying chain lengths were prepared by Suzuki coupling of the appropriate boronate ester with the corresponding dialkoxydibromonaphthalenes, followed by oxidative cyclization. Compounds 2a-i were also brominated in the 10 and 13-positions to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, several studies have shown that electron-withdrawing groups on discotic mesogens promote the formation of stable columnar liquid crystalline phases, likely through improved p-stacking interactions. [11][12][13][14] These observations suggest that the preparation of electron-decient triphenylenes may lead to discotic liquid crystals with broad mesophase ranges. Therefore, there is impetus to develop new approaches for the preparation of electron-decient triphenylene derivatives.…”
Section: Introductionmentioning
confidence: 95%
“…Furthermore, several studies have shown that electron-withdrawing groups on discotic mesogens promote the formation of stable columnar liquid crystalline phases, likely through improved p-stacking interactions. [11][12][13][14] These observations suggest that the preparation of electron-decient triphenylenes may lead to discotic liquid crystals with broad mesophase ranges. Therefore, there is impetus to develop new approaches for the preparation of electron-decient triphenylene derivatives.…”
Section: Introductionmentioning
confidence: 95%
“…Recently, several studies have demonstrated that electron-withdrawing substituents on the aromatic core of a mesogen can promote favorable self-assembly and broad columnar mesophase temperature ranges. However, although electron-withdrawing groups promote stable columnar liquid crystal phases with high clearing points, they often lead to higher melting transitions through stabilization of the solid state. , One approach to circumvent this problem is to use imide substituents, which combine an electron-withdrawing characteristic with the flexibility of an alkyl chain. We have shown that N-substituted dibenzanthracenedicarboximides ( 1 ) (Figure ) do indeed exhibit very broad liquid crystalline phases with a low melting transition due to the presence of flexible side chains and a high clearing point due to the electron-withdrawing imide groups …”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that the addition of electron-withdrawing groups to the aromatic core of a discotic molecule leads to a stabilization of the columnar mesophase, as reflected by an increase in the phase transition from the columnar phase to isotropic liquid. This stabilization of the columnar mesophase is attributed to improved π-stacking interactions. , An alternative and underutilized approach to stabilization of columnar liquid crystal phases is to exploit the tendency of aromatic and perfluoroaromatic rings to engage in strong π-stacking interactions.…”
mentioning
confidence: 99%
“…4−6 This stabilization of the columnar mesophase is attributed to improved π-stacking interactions. 4,6 An alternative and underutilized approach to stabilization of columnar liquid crystal phases is to exploit the tendency of aromatic and perfluoroaromatic rings to engage in strong πstacking interactions.…”
mentioning
confidence: 99%